Soil fertility status and sweet potato cultivation in composted mounds under humid lowland tropical climatic conditions - Patrick S. Michael (SAINS TANAH - Journal of Soil Science and Agroclimatology, 2020)
The importance of organic matter addition in composted mounds in terms of nutrients status, nutrient uptake, and environmental impact under different climatic conditions need to be studied. This study was conducted to assess the importance of Cogon grass materials addition as organic matter in composted mounds used for sweet potato cultivation on selected sandy loam soil properties under humid lowland, tropical climatic conditions. A replicated trial with four treatments with or without organic matter or sweet potato plants was set in a completely randomized design. After 6 months, soil samples were collected from two profiles in each treatment and analyzed for selected soil physiochemical properties. Data collected from each profile was pooled, averages taken, and statistically analyzed. The results showed organic matter addition increased water holding capacity and electrical conductivity, lowered soil bulk density, pH, and soil organic carbon content. Cultivation of sweet potato in soil with or without organic matter amendment, in general, depleted nitrogen, potassium, and magnesium contents and increased phosphorous availability. This study showed the addition of Cogon grass materials as organic matter in composted mounds has implications for the production of sweet potato in sandy loam soil in the tropics.